2017
DOI: 10.1016/j.antiviral.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and cytotoxicity in cell culture of novel α-hydroxytropolone inhibitors of hepatitis B virus ribonuclease H

Abstract: Chronic Hepatitis B virus (HBV) infection is a major worldwide public health problem. Current direct-acting anti-HBV drugs target the HBV DNA polymerase activity, but the equally essential viral ribonuclease H (RNaseH) activity is unexploited as a drug target. Previously, we reported that α–hydroxytropolone compounds can inhibit the HBV RNaseH and block viral replication. Subsequently, we found that our biochemical RNaseH assay underreports efficacy of the α-hydroxytropolones against HBV replication. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ]. In addition, Didierjean et al have reported that DNA polymerase activity of HIV-1 RT can be inhibited by structurally related 3,7-dHTs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ]. In addition, Didierjean et al have reported that DNA polymerase activity of HIV-1 RT can be inhibited by structurally related 3,7-dHTs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tiffany Edwards of Saint Louis University, MO, USA, reported the development of HBV RNaseH inhibitors belonging to either the N-hydroxy-isoquinolinedione (HID) and N-hydroxy-pyridinedione (HPD) families. This work follows published efforts of this team to improve the efficacy and characterize the anti-RNAse activity of these compounds in vitro (Edwards et al, 2017;Lomonosova et al, 2017). As a recall, RNAse activity in HBV polymerase is crucial for the reverse transcription of pregenomic RNA into rcDNA within nucleocapsids.…”
Section: Hepatitis and Retrovirusesmentioning
confidence: 99%
“…To identify small-molecule compounds that can inhibit the NS1N-mediated Ori cleavage, we used 96 compounds (see Table S1 in the supplemental material), which we have used previously to screen inhibitors for the RNase H nuclease activity of the human hepatitis B virus (HBV) polymerase (43)(44)(45)(46)(47), to test them for inhibitory effects on the NS1N-mediated Ori cleavage using a 32 P-labeled Ori30 template. We first tested them at 100 M and found that 25 compounds inhibited the nicking of NS1N by greater than 80%, as shown in Fig.…”
Section: Small-molecule Compounds Inhibit Cleavage Of the Ssdna Ori Bmentioning
confidence: 99%
“…In the current study, we identified 8 compounds that exhibit inhibition of NS1 nicking of the B19V Ori from the screening of 96 small-molecule compounds, which have been used to screen inhibitors of the RNase H nuclease activity of the HBV polymerase (43)(44)(45)(46)(47), using an in vitro nicking assay. We chose three compounds, compounds 7, 135, and 201, that share a similar flavonoid chemical structure for detailed study.…”
Section: B19v Ns1 Endonuclease As a Target For Anti-b19v Drugsmentioning
confidence: 99%